Changes in soft-bottom macrobenthic assemblages after a sulphuric acid spill in the Rio Grande Harbor (RS, Brazil) - C. E. Bemvenuti; J. S. Rosa-Filho; M. Elliott (Brazilian Journal of Biology)
The structure of macrobenthic assemblages in Rio Grande Harbor was analyzed during and after a sulphuric acid spill in August 1988. Five stations were sampled four times between September 1988 and March 1999. At each station, three samples were taken using a van Veen grab (0.078 m²). A total of 22 taxa were collected including Crustacea (9 spp.), Polychaeta (7 spp.), Mollusca (3 spp.), Phoronida (1 sp.), Nemertinea (1 sp.), and Plathyelminthea (1 sp.). The macrobenthic assemblages suffered different impacts depending on station location and time: 1) immediate impact, i.e., during acid discharge, as at the station nearest (250 m) the acid spill source; 2) impact some time after the discharge, as at the station 500 m downstream from the acid spill source; and 3) absence of direct impact on the remaining sampling points, on the discharge area outer limit. The macrobenthic assemblage recovered six months after the sulphuric acid spill.